Le travail de Gaignières sur les archives du Val Notre-Dame. Une porte d’entrée sur un chartrier bien conservé - Marlène Helias-Baron (Les Cahiers de l'École du Louvre)
The abbey of Val Notre-Dame was founded in around 1125 near Pontoise, in the north of the diocese of Paris, by monks from Cour-Dieu (diocese of Orléans). Thanks to the close attention of the local aristocracy, it was able to build up a substantial estate by the mid-fourteenth century. Its charter room reflect its wealth, with nearly 1,000 medieval deeds preserved. Following its incorporation into the new Feuillants order at the turn of the seventeenth century, its archives were transferred to Paris, where several inventories were drawn up. In 1693 François-Roger de Gaignières, who witnessed this institutional transformation, wrote a “cartulary” that functioned as a catalogue of the abbey’s titles. In his search for the names of the nobles of the region, he paid particular attention to the oldest deeds (twelfth and thirteenth centuries) and the seals. Including a list of abbots and drawings of burials, his work is a real port of entry to the history of Val Notre-Dame in the Middle Ages.